INTERACTION OF INNOVATION STRATEGY AND DYNAMIC CAPABILITIES IN ACHIEVING COMPETITIVE ADVANTAGE: THE MODERATING ROLE OF ENVIRONMENTAL DYNAMICS - Yuwono, Matias Andika; Ellitan, Lena (INSTITUT TEKNOLOGI DAN BISNIS PGRI DEWANTARA JOMBANG, 2025)
In a dynamic and competitive business environment, innovation strategy and dynamic capabilities are key to achieving competitive advantage. This study proposes a conceptual framework to explore the interaction between innovation strategy and dynamic capabilities, with environmental dynamism as a moderating variable. Innovation strategy enables firms to introduce new products and services that meet evolving market demands, while dynamic capabilities enable firms to adapt to environmental changes. Although the relationship between innovation strategy and competitive advantage has been recognized, there is still a gap in understanding how environmental dynamism moderates this relationship. This study aims to answer the research questions on the effect of innovation strategy on competitive advantage and dynamic capabilities, as well as the mediating role of dynamic capabilities and the moderating role of environmental dynamism. By developing and testing this conceptual framework, this study contributes to the strategic management literature by providing a deeper understanding of the conditions under which innovation strategy effectively achieves competitive advantage. In addition, this study offers practical insights for managers on aligning innovation strategy with dynamic capabilities to navigate complex business environments. The findings are relevant to firms operating in increasingly complex and dynamic business environments and provide directions for future research exploring the interaction between internal and external factors in determining the success of innovation strategies.